To the issue of historiography of Sofia Rusova work legacy research - Zaichenko, Ivan (Pedagogical Discourse, 2013)
Sofia F.Rusova (nee Lindfors) (1856-1940) was a teacher, writer, journalist, Doctor of Sociology at the Ukrainian Sociological Institute, Professor of Pedagogy at the M.P.Dragomanov Ukrainian High Pedagogical Institute in Prague, Czechoslovakia, head of the preschool and extra-school education department in the Government of the Ukrainian Peopleʼs Republic (1917-1921), head of the Ukrainian branch of the International Womenʼs Organization, organizer of the first kindergarten in Ukraine and well-known public figure of her era. She has left a rich pedagogical heritage (more than 300 of her works have been currently introduced into scientific use) that contains many interesting ideas, notions and conclusions on topical issues of public education, pedagogy, national schooling and education. The historiography of Sofia Rusova (1856-1940) work legacy research in Ukraine, starting from the first articles (1991) and up to the last one in 2012 was revealed in the article. Specific research works were analysed and their essential provisions were identified.